Identifikasi Jamur Patogen Penyebab Penyakit Layu Pucuk pada Tanaman Adenium spp. di Kota Denpasar dan Potensi Pengendaliannya dengan Jamur Antagonis - DWI SUGIARTA; I PUTU SUDIARTA; NI WAYAN SUNITI; I PUTU WIRYA SUPUTRA (Program Studi Agroekoteknologi, Fakultas Pertanian, Universitas Udayana, 2021)
Identification of Pathogenic Fungi that cause Wilting Diseases on Adenium spp. Shoot in Denpasar City and the Potential Control with Antagonistic Fungi Ornamental plants of Adenium, known as kamboja Jepang have various types of flowers and stem shapes and have become unique ornamental plants in Indonesia. Adenium plants that grow in Denpasar City showed the symptoms of pathogenic fungi like wilting on the shoots. This study aims to identify the pathogenic fungi that cause major diseases in Adenium spp. in the area of ??Denpasar City. The activities carried out in this study were (1) sampling, (2) isolation of the pathogenic fungi from symptomatic Adenium plant, (3) pathogenicity test, (4) morphological identification of pathogenic fungi, and (5) inhibition test of the antagonistic fungi against the pathogenic fungi. This research was conducted in Denpasar City and the Plant Disease Laboratory, Faculty of Agriculture, Udayana University. The results of this study were successful in identifying Fusarium sp. as a pathogen that causes wilting of the shoots or dieback. The potential for biological control by utilizing antagonistic fungi showed that Gliocladium sp. can suppress the growth of pathogenic fungi Fusarium sp. up to > 87% and Trichoderma sp. up to > 88 %.